Hubungan Religiusitas dan Interaksi Orangtua dengan Perkembangan Moral Siswa Sekolah Menengah Atas Negeri 20 Medan - Abdul Malik; Nur Aini; Abrar Parinduri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to examine the relationship between religiosity and parental interaction with the moral development of students at State Senior High School 20 Medan. This study uses a quantitative approach with the analysis technique of Multiple Regression Analysis. Obtaining sampling using random sampling obtained a sample of 186 people. Data collection techniques used three scales, namely the scale of religiosity, parental interaction, and moral development. This study concludes that (1) there is a significant positive correlation between religiosity and moral development where r_xy= 0.590 with p = 0.000, the coefficient r^2=0.348, which means that religiosity contributes 34.8% to form moral development. (2) there is a significant positive correlation between parental interaction and moral development where r_xy = 0.731 with p = 0.000 means p < 0.050, the coefficient of determinant (r^2) r^2 = 0.535 which means parent interaction contributes 53.5% to form moral development.